ANALISIS PENGARUH BERBAGAI MACAM MERK OLI TERHADAP TEMPERATUR MESIN YAMAHA VIXION 150CC - Aris Budi Perlindungan; Aqli Mursadin (Scientific Journal of Mechanical Engineering Kinematika, 2017)
This study aims to determine the effect of various brands of oil against temperature, exhaust emissions, and performance on the engine yamaha vixion 150cc. This study was conducted by taking temperature data, exhaust emissions, and engine performance yamaha vixion 150cc. This research uses three different types of oil, namely super yamalube sport oil, ax7 advanced shell, and pertamina enduro. Temperature testing is performed at engine speed of 1,500 rpm, 4000 rpm and 10,500 rpm using neutral gear, 1, 2, 3, 4, and 5. Performance tests are performed using a dyno test for one test of each type of oil. Once the data in can and in the past compared the results of temperature data, exhaust emissions, and the performance of each type of oil. The best oil temperature test result is using yamalube oil. Testing the lowest exhaust gas emission gas emissions are advanced Ax7 shell oil. Ax7 shell oil produces the lowest exhaust emissions among other oils while enduro oil exceeds the standard exhaust emission limits of CO at 10,500 rpm to 5.42% while the standard is 4.50%. Testing the best performance is using enduro oil because enduro oil can produce the greatest power 13.55 Hp.